Design of e-shoe for Visually Impaired by Using RFID Technology - Dr P V Subbaiah; Shireen Anjum; R Umasree; T Amuktha Mala; R Sharika Deepthi (Journal of Electronic Design Engineering, 2017)
It is a known fact that blind people find it extremely difficult to detect their way through obstacles and stairs. Using a white stick to detect the obstacles had been an age old method, which cannot provide complete solution. In order to overcome this problem, an obstacle detecting shoe is developed. It senses the obstacle through ultrasonic sensors and alerts the user through the message. The ultrasonic waves transmitted are reflected by the obstacles and echo is received by the ultrasonic receiver, where the distance is calculated by using a microprocessor. The RFID system is used to assist the blind people. When the reader located on the shoe moves on to a specific tag, unique tag ID is sent to the reader. While in the case of walking in traffic, RF Link Transmitter/receiver is used for traffic signal detection and for passing instructions to the user through voice messages. A timer is used to detect the wet areas and helps the blind to avoid slippery.